2014
DOI: 10.1111/hepr.12403
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of balloon‐occluded transcatheter arterial chemoembolization using miriplatin for hepatocellular carcinoma

Abstract: Compared with C-TACE, B-TACE significantly improved cancer nodule control, and it was satisfactory in terms of safety. B-TACE is an effective procedure that enhances the effects of catheterization with miriplatin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
59
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(67 citation statements)
references
References 6 publications
6
59
0
2
Order By: Relevance
“…This is possibly because the number of patients in our EPIR-C-TACE group who could be treated with superselective TACE might have been fewer than in previous reports. The local control rate after MPT-B-TACE in the present study (median time to local recurrence, 8.3 M) might be comparable with previous reports regarding C-TACE using MPT and EPIR [14,32], but the present data tended to be lower than in previous reports regarding MPT-B-TACE [28,33,34]. This might be possibly caused by patient and tumor characteristics.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…This is possibly because the number of patients in our EPIR-C-TACE group who could be treated with superselective TACE might have been fewer than in previous reports. The local control rate after MPT-B-TACE in the present study (median time to local recurrence, 8.3 M) might be comparable with previous reports regarding C-TACE using MPT and EPIR [14,32], but the present data tended to be lower than in previous reports regarding MPT-B-TACE [28,33,34]. This might be possibly caused by patient and tumor characteristics.…”
Section: Discussionsupporting
confidence: 85%
“…The rate of IR in the present study tended to be lower than that in Miyayama's report. Recent studies regarding MPT-B-TACE reported a high objective response rate, including TE3 and TE4, after treatment [28,29]. The main strength of B-TACE might be the forceful injection of MLS after its accumulation in the treated arteries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When obvious progression is shown by imaging, prompt switching of the therapeutic modality is recommended. In other words, attempts to perform a few additional TACE procedures by changing catheter devises such as a balloon catheter [21], a chemoagent, or embolization switching devises (e.g. drug-eluting beads) [22] can be considered until the tumor marker score increases to ≥2 in cases considered as having stable disease or with a slow progression in imaging findings.…”
Section: Discussionmentioning
confidence: 99%
“…Irie et al [12] reported that better lipiodol deposition was obtained by performing selective TACE while decreasing the inflow resistance of intratumoral blood flow using a microballoon catheter, called ‘balloon-occluded TACE' (b-TACE). There are reports that b-TACE has the potential to improve cancer nodule control locally, compared with c-TACE [13,14]. …”
Section: Introductionmentioning
confidence: 99%